GEOMORPHOLOGIC AND STRATIGRAPHIC DETERMINATION USING OUTCROP DATA, THIN SECTION AND MICROFOSSIL ANALYSIS IN BENTARSARI AREA, BREBES DISTRICT, CENTRAL JAVA - Dewi, Viska Triaraminta; Nurdrajat, Nurdrajat; Firmansyah, Yusi; Fachrudin, Kurnia Arfiansyah (Journal of Geological Sciences and Applied Geology, 2018)
Administratively, Bentarsari area was located in Salem Sub-District and Brebes District in Central Java Province with coordinate 108°46’45,15” - 108°49’28.29” BT - 108°39’32.4” BT and 7°7’40.34” LS - 7°10’22.22” LS.  This research aims is to give an understanding about geological condition in geomorphology and stratigraphy aspects which are described by thematic map in 1:12.500 scale within an area of 25km2. This research was accomplished with surface data (outcrop) and field orientation method using of GPS, geological compass, loop, geological hammer, comparator, and any other tools. Afterward, thin section and fossil analysis were also collected to determine the type of rocks and the age of the stratigraphy unit. This research will include the classification of geomorphology unit based on 3 aspects, which are morphography,  morphometry, and morphogenetic and also classification of stratigraphy unit, based on characteristics of rocks such as rock texture, mineral contents and fossil contents. The geomorphology of the Bentarsari region can be divided into 3 (three) geomorphological units, namely: the alluvium high altitude fluvial unit, high hills of steep structural sediments unit, and very steep high structural sedimentary hills unit. While the Litho-stratigraphic on research area divided into 4 (four) units, from the oldest to the youngest stratigraphy position is sandstone unit (Tbp), claystone unit (Tbl), fine-grained sandstone unit (Tpbph), and breccia unit (Qpbx). Thus, by having the result of this research, can be useful as a reference to have further studies in this located area.